KAJIAN TEKNOLOGI IRADIASI BERKAS ELEKTRON PADA LIMBAH CAIR PRA PENYAMAKAN KULIT MENJADI PUPUK ORGANIK CAIR - Cahya Widiyati; Herry Poernomo (Politeknik ATK Yogyakarta, 2017)
Technology study of electron beam irradiation on the liquid waste of pre tanning become liquid organic fertilizer has been done. Objective of this study is to obtain manufacture method of electron beam irradiation on the liquid waste of pre tanning become liquid organic fertilizer. Process of irradiation on the liquid waste of pre tanning is for detoxification of H2S, disinfection of bacteria pathogen, and decomposition of organic compound (protein) so that ratio of C/N less 30. Result of study shows that smaller air gap (tu) or distance of window to surface of liquid waste film of pre tanning above belt conveyor showing that production capacity of liquid waste after irradiation even greater. At process conditions: e-beam energy E = 0.3 MeV, e-beam current I = 20 mA, tu = 5 cm, and absorbed dose D = 100 kGy it is obtained production capacity of liquid waste after irradiation m = 543.8941 ton/year. At the same condition with E going up to 1.5 MeV, it is obtained that m = 2,886.2444 ton/year. Liquid waste of pre tanning from irradiation result contains macro nutrition that can be used as raw material on the manufacture of liquid organic fertilizer by method of aerobe fermentation using effective microorganism.